Modelagem matemática e o Documento Curricular para Goiás etapa Ensino Médio (DC-GOEM): contribuições para o ensino de matemática no ensino médio - Santos, Lidiane Rodrigues da Mata (2024)
This dissertation investigates the use of Mathematical Modeling in high school, focusing on compliance with the Curricular Document for Goiás (DC-GOEM), and its contributions to mathematics teaching. Given students' difficulties in understanding mathematical concepts, the need for methods that make learning more engaging and relevant to their daily lives, simultaneously, make it possible to fulfill the curriculum proposed by DC-GOEM/Bimonthly in the Public Education Network in Goiás, constitutes the core of the research. Based on the concepts of Mathematical Modeling presented by Bassanezi, Biembengut, Barbosa and Burak, after extensive bibliographical research in the dissertation database of the Professional Master's Degree in Mathematics on a National Network - PROFMAT, we selected works that can contribute to the improvement of mathematics teaching in the presented. The analysis of these dissertations aimed to identify the concepts used by the authors, main difficulties, advantages, content covered, skills and learning objectives addressed. In the latter, in particular, the analysis revealed that the DC-GOEM Learning Objectives, at different moments in high school, can be achieved with the Mathematical Modeling methodology, providing significant learning of mathematical concepts applied to real situations in everyday life of students. Furthermore, the variety of content covered and the difficulties and advantages highlighted by each author serve as a guide for teachers interested in using Mathematical Modeling. Therefore, we understand that this work contributes to the improvement of Mathematics Teaching, at the Secondary level, by offering teachers from the State Education Network of Goiás, a detailed analysis of works that used Mathematical Modeling and achieved the Learning Objectives set out in the DC- GOEM/Bimonthly. We believe that this knowledge can lead teachers to adopt Mathematical Modeling in their classrooms, promoting more integrated and meaningful teaching.